Computed tomography (CT) head studies in a district emergency department: a focused study of CT related imaging and analysis of current practice - Lesar, Ursula (Division of General Surgery, 2022)
Introduction: The South African population has a significant emergency burden of disease. In South Africa, immediate access to computed tomography (CT) imaging may not always be available. Globally, the number of all imaging studies is increasing annually. Due to access challenges patients requiring CT head imaging needs to be carefully selected to ensure safe management and discharge. Patient demographics, clinical presentation and type of expected emergency pathology known about this population will assist the emergency physician in making appropriate management decisions. Methodology: This study was conducted in two parts: a literature review and a retrospective, descriptive analysis conducted at Mitchells Plain Hospital, Cape Town, exploring the type and prevalence of pathology identified by CT head imaging in the emergency department. Data for the descriptive study was collected over a one-year period and the demographics, indications and reported pathology were described for all CT head requests in the emergency department. Statistically significant differences between groups were calculated using the Chi-squared test, depending on the sample characteristics. Statistical significance was defined as p-value <0.05. Results: There was a male predominance (57%) in this study with the most common comorbidity being hypertension. The cumulative yield of pathology was identified at 58% on imaging (new pathology 40% and existing pathology 18%). Stroke (32%), trauma (30%) and seizures (16%) were the most common indications for imaging with a yield per indication of 54%, 48% and 20% respectively. The most common imaging finding across all categories was an ischaemic stroke. Stroke indicated CT head imaging pathology demonstrated ischaemic (19%) to haemorrhagic (3%) stroke pathology. The most common finding on a trauma indicated CT head was an ischaemic stroke (13%). Seizure indicated CT head imaging demonstrated 18% with new pathology and 36%that had existing pathology. Emergency imaging was performed on average under seven hours post consultation. Conclusion: Acquiring CT head imaging in a resource limited setting requires appropriate clinical history, examination as well as awareness of the most prevalent pathology of the community the doctor is treating. Even though yield of pathology was considered high when compared to HIC there was similarity in yield to local and international LMICs. Stroke, trauma and seizures are common indications for imaging in the South African setting with the most common pathology identified to be an ischaemic stroke.